SYSTEMATIC LITERATURE REVIEW: RISK MANAGEMENT IN THE CHILEAN SUPPLY CHAIN - Imro, Imro Atus Solikhah; Wakhidati, Yusmi Nur; Lestari, Sri (Jurnal Hexagro, 2026)
The chili supply chain is a complex system vulnerable to risks at every stage, from production to marketing. High climate uncertainty, pest and disease attacks, price fluctuations, and limited distribution systems make chili one of the horticultural commodities with high price volatility in Indonesia. This study aims to systematically review prior studies on risk management in the chili supply chain. The method used is a Systematic Literature Review (SLR). Literature searches were conducted using Google Scholar, Publish or Perish, and ResearchGate, with predetermined inclusion and exclusion criteria. The study's results indicate that production and price risks are the most dominant in the chili supply chain. The main sources of risk come from climate factors, low adoption of cultivation technology, the length of the marketing chain, and price information asymmetry. The most commonly used analytical methods in previous studies are qualitative descriptive approaches, supply chain analysis, and value chain analysis, while the application of more structured risk analysis methods is still limited. Commonly recommended risk mitigation strategies include diversifying marketing channels, improving coordination among supply chain actors, implementing more advanced cultivation technologies, and strengthening farmer institutions. Overall, the SLR results indicate that risk management in the chili supply chain remains partial and not fully integrated, underscoring the need for a more comprehensive and sustainable risk management model.